2014
DOI: 10.4149/neo_2014_059
|View full text |Cite
|
Sign up to set email alerts
|

High TBX2 expression predicts poor prognosis in non-small cell lung cancer

Abstract: Deregulated expression of T-box2 (TBX2) has been implicated in malignancies. However, the expression pattern and the role of TBX2 in non-small cell lung cancer (NSCLC) remain unclear. The aim of this study was to explore the clinical value of TBX2 in patients with NSCLC. We examined TBX2 expression in 40 NSCLC tissues and matched adjacent noncancerous tissues by quantitative RT-PCR (qRT-PCR) and Western blotting. Furthermore, the TBX2 protein expression was analyzed by immunohistochemistry in 416 NSCLC samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
1
10
1
Order By: Relevance
“…TBX2 may serve as a prognostic factor of breast cancer (7,9), melanoma (8), gastric cancer (10), prostate cancer (11), laryngeal squamous cell carcinoma (12), and non-small cell lung cancer (14). TBX2 is associated with resistance to therapeutic drugs such as cisplatin and doxorubicin (15,16), and TBX2 therefore may serve as a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TBX2 may serve as a prognostic factor of breast cancer (7,9), melanoma (8), gastric cancer (10), prostate cancer (11), laryngeal squamous cell carcinoma (12), and non-small cell lung cancer (14). TBX2 is associated with resistance to therapeutic drugs such as cisplatin and doxorubicin (15,16), and TBX2 therefore may serve as a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…TBX2 is overexpressed by numerous human cancers (7)(8)(9)(10)(11)(12)(13)(14). TBX2 may serve as a prognostic factor of breast cancer (7,9), melanoma (8), gastric cancer (10), prostate cancer (11), laryngeal squamous cell carcinoma (12), and non-small cell lung cancer (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier reports have suggested that expression levels of TBX2 are elevated in NSCLC [ 39 , 40 ]. The reports by Hu et al [ 39 ] and Zhang et al [ 40 ] interrogated TBX2 protein by immunohistochemistry in NSCLCs alone (tissue microarrays) and suggested that tumors with relatively high expression of the protein (based on percent positivity within the tumors themselves) exhibited comparatively poor prognosis [ 39 , 40 ]. The same reports studied expression levels of the TBX2 gene (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The same reports studied expression levels of the TBX2 gene (e.g. by quantitative real-time PCR) in NSCLCs and paired normal lung tissues in a smaller subset of NSCLC cases ( n = 40 to 50) [ 39 , 40 ] demonstrating that the gene is elevated in the tumors. These earlier studies [ 39 41 ], albeit few, point to putative oncogenic roles and properties for the TBX2 gene in human NSCLC.…”
Section: Discussionmentioning
confidence: 99%